Analytical and simulation model of fighter flight dynamics with a limiter for the permissible flight envelope when performing the split-S maneuver - P. S. Kostin; K. A. Zhuravskiy (Научный вестник МГТУ ГА, 2023)
The article substantiates the relevance to develop an analytical-simulation model of fighter flight dynamics with a limiter for the permissible flight envelope during the split-S maneuver. The structure of the analytical and simulation model of a fighter, consisting of a combination of a flight test bench, a model of fighter flight dynamics, a model of an astatic limiter for the permissible flight envelope and a model of pilot control actions based on the theory of fuzzy sets, is presented. The structure of the model of fighter flight dynamics with a limiter for the permissible flight envelope, consisting of a system of differential and algebraic equations, a model of an integrated control system, a geometry, mass and balance unit, a unit for calculating aerodynamic forces, a power plant unit, a bank of aerodynamic performance, a unit for calculating feedback on efforts from flight controls, is presented. The model differs from the known ones by the availability of the split-S simulation unit, which is designed for the split-S simulation and the multi-iteration split-S simulation with different initial conditions to determine the basic split-S parameters, the kinematic flight operation performance and to construct the split-S implementation area. The split-S simulation unit comprises the specified value functions, a pilot control actions model, a unit for processing simulation results, a unit for determining the basic split-S parameters, and a database of operating modes. The specified value functions determine the specified values of the kinematic aircraft movement parameters, which are used to implement control in various phase coordinates of the maneuver. The model makes it possible to obtain reliable values of the kinematic fighter movement parameters under the semi-natural simulation with the participation of the pilot and the simulation split-S maneuver modeling using the pilot control actions model.